Listen NCERT Audio Books to boost your productivity and retention power by 2X.

4

If the sum of the zeros of the polynomial f(x) = 2x^{3} – 3kx^{2} + 4x – 5 is 6, then the value of k is

Given,

f(x) = 2x^{3} – 3kx^{2} + 4x – 5

Sum of the zeros of the polynomial = 6

Let x, y and z be the zeroes than,

x + y + z = 6……Equation (i)

So,

x + y + z = – b/a

= – ( – 3k)/2

From Eq. (i) we get,

3k/2 = 6

k/2 = 6/3

k = 2×2 = 4

8

The sum and product of the zeros of a quadratic polynomial are and — 3 respectively. What is the quadratic polynomial?